Multilayer integral photo-thermal catalyst as well as preparation method and application thereof

Through the design of a multi-layer integrated photothermal catalyst, the combination structure of nickel foam and magnesium oxide and the cocatalyst of cerium-zirconium solid solution is solved, and the problems of low solar energy utilization and slow reaction kinetics in photocatalytic CO2 conversion are achieved with high efficiency The photothermal catalytic CO2 reduction is suitable for the preparation of carbon and hydrocarbon fuel in concentrated photothermal systems.

CN119114085APending Publication Date: 2024-12-13SOUTHEAST UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411119735.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing photocatalytic CO2 conversion catalysts have problems such as low solar energy utilization, slow photocatalytic reaction kinetics and weak adsorption ability of reactant molecules, which leads to the high challenges in the actual production and application of photocatalytics.

Method used

Multi-layer integrated photothermal catalyst is used, consisting of a photothermal conversion layer, an insulation layer and a photothermal catalytic layer. The photothermal conversion layer is foam nickel, the insulation layer is magnesium oxide, and the photothermal catalytic layer is a cerium-zirconium solid solution containing a cocatalyst. , through chemical bond connection, the infrared absorption performance of nickel foam and the thermal insulation effect of magnesium oxide are used, combined with the regulation of non-precious metal cocatalysts, improve the photothermal catalytic effect and reactant adsorption capacity.

Benefits of technology

The photothermal effect and the adsorption capacity of reactant molecules were significantly improved, and the performance of photocatalytic CO2 reduction reaction was improved. The yields of CO and CH4 reached the highest 109.13μmol·g-1·h-1 and 145.27μmol·g-1·g-1·g-1·g-1·, respectively. h-1, suitable for large-scale production and application in concentrated photothermal systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114085A_ABST
    Figure CN119114085A_ABST
Patent Text Reader

Abstract

The invention discloses a multilayer integral photo-thermal catalyst as well as a preparation method and application thereof. The catalyst comprises a photo-thermal conversion layer, a heat preservation layer and a photo-thermal catalytic layer from inside to outside, the photo-thermal conversion layer is made of foamed nickel, the heat preservation layer is made of magnesium oxide, and the photo-thermal catalytic layer is made of cerium-zirconium solid solution containing a promoter; the photo-thermal conversion layer absorbs low-energy photons and effectively converts solar energy into heat energy; the heat preservation layer reduces dissipation of heat energy and provides active sites for reactant molecules; the photo-thermal catalytic layer absorbs high-energy photons to carry out photocatalytic CO2 reduction reaction, is used in a light-gathering photo-thermal system, can utilize solar energy in a gradient manner, and shows excellent light-gathering photo-thermal coupling catalytic CO2 reduction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a monolithic catalyst, in particular to a multi-layer monolithic photothermal catalyst, and also to a preparation method and application of the monolithic catalyst. Background Art

[0002] As a green and sustainable technology, photocatalytic CO2 conversion into hydrocarbon fuels is a potential solution to energy shortages and global warming. However, limitations such as low solar energy utilization, slow kinetics of photocatalytic reactions, and weak adsorption capacity of reactant molecules make the actual production application of photocatalysis highly challenging. Photothermal catalysis integrates solar-mediated photochemical processes and solar-induced thermal catalysis into a unit, forming a complementary and synergistic effect, which greatly improves the catalytic activity. Therefore, photothermal catalytic CO2 reduction technology has greater research potential and application value.

[0003] In recent years, materials that can absorb the entire solar spectrum for photothermal conversion have attracted widespread attention, such as foamed metals, Fe-based materials, MXenes (carbides, nitrides, carbonitrides), graphene, defective metal oxides, and polydispersed precious metal nanoparticles. However, the heat energy converted by them will cause a temperature gradient between the catalyst and the surrounding environment due to the lack of an insulating shell, causing heat to be dissipated from the photothermal conversion material to the surrounding environment. Therefore, there is still a need to improve photothermal catalysts to more efficiently collect and utilize solar energy.

[0004] The invention patent with publication number CN115518641A quickly grows zinc oxide nanoarrays on a nickel foam substrate through a one-step hydrothermal method, but the catalytic material cannot divide the frequency of sunlight and therefore cannot achieve efficient solar energy utilization efficiency. The invention patent with publication number CN116689013A grows a layer of titanium nitride as a photothermal layer in situ on nickel foam by focusing, and then grows a metal oxide photoelectric layer and metal nanoparticles on the titanium nitride photothermal layer through further illumination. However, the catalytic material can only produce a weak photothermal effect and does not significantly improve the photocatalytic performance. Therefore, the existing photocatalytic CO2 conversion catalysts still have problems such as low solar energy utilization, slow kinetics of photocatalytic reactions, and weak adsorption capacity of reactant molecules that need to be solved. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a multi-layered integral photothermal catalyst with high energy conversion rate and fast catalytic reaction, and also to provide a preparation method of the above-mentioned integral catalyst and its application in the preparation of hydrocarbon fuels in a concentrated photothermal system.

[0006] Technical solution: The multi-layered integral photothermal catalyst of the present invention comprises, from the inside to the outside, a photothermal conversion layer, a thermal insulation layer and a photothermal catalytic layer, wherein the photothermal conversion layer is nickel foam, the thermal insulation layer is magnesium oxide, and the photothermal catalytic layer is a cerium-zirconium solid solution containing a promoter.

[0007] Wherein, the promoter is a non-precious metal, specifically one or a combination of two of nickel, copper, cobalt, iron or manganese.

[0008] The molar ratio of the nickel foam, magnesium oxide, cerium-zirconium solid solution and promoter is 1000-10000:10-100:5-15:0.5-1.5.

[0009] Among them, the photothermal conversion layer is a porous skeleton open structure with a large number of connecting holes, the thermal insulation layer is a nano-sheet structure, and the photothermal catalytic layer is irregular nanoparticles; the photothermal conversion layer, the thermal insulation layer and the photothermal catalytic layer are connected by chemical bonds.

[0010] The preparation method of the above-mentioned monolithic catalyst comprises the following steps:

[0011] (1) placing nickel foam in a magnesium chloride aqueous solution, adjusting the pH value of the solution, stirring, taking out and performing high-temperature annealing in a nitrogen atmosphere to obtain nickel foam@magnesium oxide;

[0012] (2) placing the nickel@magnesium oxide foam obtained in step (1) in a mixed solution of cerium nitrate, zirconium oxychloride and sodium hydroxide, stirring the mixture thoroughly and then performing a hydrothermal treatment. After the reaction is completed, the mixture is taken out and washed and dried to obtain a nickel@magnesium oxide foam@cerium-zirconium solid solution;

[0013] (3) placing the nickel foam @ magnesium oxide @ cerium zirconium solid solution obtained in step (2) in a mixed solution of non-precious metals and hydrazine hydrate, stirring the reaction sufficiently and then performing hydrothermal treatment. After the reaction is completed, the solid solution is taken out and washed and dried to obtain an integral catalyst for photothermal catalytic CO2 reduction.

[0014] Wherein, in step (1), the solution pH is adjusted to 9-11, the stirring time is 1-5 hours, the concentration of the magnesium chloride aqueous solution is 0.1-1.0 mol / L, and the annealing temperature is 150-250° C. and the time is 1-5 hours.

[0015] Wherein, in step (1), the nickel foam may also be pretreated, specifically by ultrasonic cleaning with anhydrous ethanol and deionized water, and rinsing with a dilute hydrochloric acid solution to remove surface oxides and unnecessary impurities, and finally vacuum drying.

[0016] Wherein, in step (2), the molar ratio of cerium nitrate to zirconium oxychloride is 1:1-3, the molar ratio of the total molar ratio of cerium nitrate and zirconium oxychloride to sodium hydroxide is 1:1-3, and the stirring time is 1-5 hours; the temperature of the hydrothermal treatment is 100-200°C, and the time is 4-8 hours.

[0017] Wherein, in step (3), the molar ratio of the non-precious metal to hydrazine hydrate is 1:1-3, the temperature of the hydrothermal treatment is 100-140°C, and the time is 8-12h.

[0018] The above-mentioned monolithic catalyst for photothermal catalytic CO2 reduction can also be used in concentrated photothermal systems to prepare hydrocarbon fuels.

[0019] The multi-layered integral photothermal catalyst is used for photothermal catalytic CO2 reduction reaction to prepare hydrocarbon fuels.

[0020] Principle of the invention: The multi-layer integral photothermal catalyst of the present invention, wherein the photothermal conversion layer is nickel foam, which exhibits good infrared absorption performance, can absorb low-energy photons and effectively convert solar energy into thermal energy; the thermal insulation layer, on the one hand, uses its heat insulation and infrared shielding effects to limit the heat energy generated by the nickel foam therein to reduce the dissipation of heat energy and form a "greenhouse effect", and on the other hand, provides a large number of active sites for the adsorption of the reactant molecule CO2, thereby promoting the reduction of CO2 in the photothermal catalyst layer; the regulation of the non-precious metal co-catalyst makes the cerium-zirconium solid solution in the photothermal catalyst layer have a suitable energy band structure, which can absorb high-energy photons for photocatalytic CO2 reduction reaction.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The multi-layered monolithic photothermal catalyst of the present invention can effectively improve the photothermal effect and strengthen the adsorption of reactant molecules, thereby improving the performance of the photocatalytic CO2 reduction reaction. It is applied in the concentrated photothermal system to prepare hydrocarbon fuels, and the CO yield can reach up to 109.13 μmol·g -1 ·h -1 The maximum yield of CH4 can reach 145.27 μmol·g -1 ·h -1 (2) The preparation method of the multi-layered integral photothermal catalyst of the present invention is simple and easy to operate, suitable for large-scale production, and has broad prospects in practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is an operation flow chart of the present invention;

[0023] Figure 2 The nickel@MgO@Ce foam prepared in Example 1 of the present invention 0.25 Zr 0.75Scanning electron microscope image of nickel foam in the photothermal conversion layer of O2 / Ni;

[0024] Figure 3 The nickel@MgO@Ce foam prepared in Example 1 of the present invention 0.25 Zr 0.75 SEM image of MgO in the insulation layer of O2 / Ni;

[0025] Figure 4 The nickel@MgO@Ce foam prepared in Example 1 of the present invention 0.25 Zr 0.75 Ce in the photothermal catalyst layer of O2 / Ni 0.25 Zr 0.75 Scanning electron microscope image of O2 / Ni. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.

[0027] Example 1

[0028] The multi-layered monolithic photothermal catalyst of the present invention comprises the following steps:

[0029] (1) 0.5 g of the pretreated nickel foam was placed in a 100 mL aqueous solution containing 6.099 g of magnesium chloride hexahydrate and stirred, and then ammonia water was added dropwise to adjust the pH of the solution to 10, and stirred for 3 h. The foam was then taken out and subjected to high temperature annealing treatment at 200 ° C for 3 h in a nitrogen atmosphere to obtain nickel foam @MgO.

[0030] (2) The foamed nickel@MgO was placed in a 100 mL aqueous solution containing 1.086 g of cerium nitrate hexahydrate, 2.417 g of zirconium oxychloride octahydrate and 0.400 g of sodium hydroxide, stirred for 1 h, and then all transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 150°C for 6 h. After the reaction was completed, the foamed nickel@MgO@Ce was taken out, washed with deionized water and vacuum dried to obtain the foamed nickel@MgO@Ce 0.25 Zr 0.75 O2.

[0031] (3) Foam nickel@MgO@Ce 0.25 Zr 0.75 O2 was placed in a 100 mL aqueous solution containing 0.145 g nickel nitrate hexahydrate and 0.025 g hydrazine hydrate, stirred for 30 min, and then the sample and the mixed solution were transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 120 ° C for 10 h. After the reaction was completed, the sample was taken out and washed with deionized water and dried in vacuum to obtain foamed nickel@MgO@Ce 0.25Zr 0.75 O2 / Ni.

[0032] Example 2

[0033] The multi-layered monolithic photothermal catalyst of the present invention comprises the following steps:

[0034] (1) 0.5 g of the pretreated nickel foam was placed in a 100 mL aqueous solution containing 6.099 g of magnesium chloride hexahydrate and stirred, and then ammonia water was added dropwise to adjust the pH of the solution to 10, and stirred for 3 h. The foam was then taken out and subjected to high temperature annealing treatment at 200 ° C for 3 h in a nitrogen atmosphere to obtain nickel foam @MgO.

[0035] (2) The nickel@MgO foam was placed in a 100 mL aqueous solution containing 2.171 g of cerium nitrate hexahydrate, 1.611 g of zirconium oxychloride octahydrate and 0.400 g of sodium hydroxide, stirred for 1 h, and then all transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 150°C for 6 h. After the reaction was completed, the foam was taken out, washed with deionized water and vacuum dried to obtain nickel@MgO@Ce foam. 0.5 Zr 0.5 O2.

[0036] (3) Foam nickel@MgO@Ce 0.25 Zr 0.75 O2 was placed in a 100 mL aqueous solution containing 0.145 g nickel nitrate hexahydrate and 0.025 g hydrazine hydrate, stirred for 30 min, and then the sample and the mixed solution were transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment at a temperature of 120 ° C and a hydrothermal time of 10 h in an oven. After the reaction was completed, the sample was taken out, washed with deionized water and vacuum dried to obtain foamed nickel@MgO@Ce 0.5 Zr 0.5 O2 / Ni.

[0037] Example 3

[0038] The multi-layered monolithic photothermal catalyst of the present invention comprises the following steps:

[0039] (1) 0.5 g of the pretreated nickel foam was placed in a 100 mL aqueous solution containing 6.099 g of magnesium chloride hexahydrate and stirred, and then ammonia water was added dropwise to adjust the pH of the solution to 10, and stirred for 3 h. The foam was then taken out and subjected to high temperature annealing treatment at 200 ° C for 3 h in a nitrogen atmosphere to obtain nickel foam @MgO.

[0040] (2) The nickel@MgO foam was placed in a 100 mL aqueous solution containing 1.086 g of cerium nitrate hexahydrate, 2.417 g of zirconium oxychloride octahydrate and 0.400 g of sodium hydroxide, stirred for 1 h, and then transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 150°C for 6 h. After the reaction was completed, the foam was taken out, washed with deionized water and vacuum dried to obtain nickel@MgO@Ce foam. 0.25 Zr 0.75 O2.

[0041] (3) Foam nickel@MgO@Ce 0.25 Zr 0.75 O2 was placed in a 100 mL aqueous solution containing 0.145 g nickel nitrate hexahydrate, 0.146 g cobalt nitrate hexahydrate and 0.025 g hydrazine hydrate, stirred for 30 min, and then the sample and the mixed solution were transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 120 ° C for 10 h. After the reaction was completed, the sample was taken out, washed with deionized water and vacuum dried to obtain foamed nickel@MgO@Ce 0.25 Zr 0.75 O2 / NiCo.

[0042] Comparative Example 1

[0043] A catalyst, compared with the embodiment, without providing a heat-insulating layer:

[0044] (1) 0.5 g of the pretreated nickel foam was placed in a 100 mL aqueous solution containing 1.086 g of cerium nitrate hexahydrate, 2.417 g of zirconium oxychloride octahydrate and 0.400 g of sodium hydroxide, stirred for 1 h, and then transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 150 ° C for 6 h. After the reaction was completed, the foam was taken out, washed with deionized water and vacuum dried to obtain nickel foam @ Ce 0.25 Zr 0.75 O2.

[0045] (2) Foam nickel@Ce 0.25 Zr 0.75 O2 was placed in a 100 mL aqueous solution containing 0.145 g nickel nitrate hexahydrate, 0.146 g cobalt nitrate hexahydrate and 0.025 g hydrazine hydrate, stirred for 30 min, and then the sample and the mixed solution were transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 120 ° C for 10 h. After the reaction was completed, the sample was taken out, washed with deionized water and vacuum dried to obtain foamed nickel@Ce 0.25 Zr 0.75 O2 / NiCo.

[0046] Comparative Example 2

[0047] A catalyst, compared with the embodiment, the insulation layer is set to SiO2:

[0048] (1) 0.5 g of the pretreated nickel foam was placed in an alcohol solution containing 0.521 g of ethyl orthosilicate and stirred for 30 min, then ammonia water was added dropwise to adjust the pH of the solution to 10, and stirred for 3 h. The foam was then taken out and subjected to high temperature annealing treatment at 200°C for 3 h in a nitrogen atmosphere to obtain nickel foam@SiO2.

[0049] (2) The nickel @ SiO2 foam was placed in a 100 mL aqueous solution containing 1.086 g of cerium nitrate hexahydrate, 2.417 g of zirconium oxychloride octahydrate and 0.400 g of sodium hydroxide, stirred for 1 h, and then transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 150 ° C for 6 h. After the reaction was completed, the foam was taken out, washed with deionized water and vacuum dried to obtain nickel @ SiO2 @ Ce 0.25 Zr 0.75 O2.

[0050] (3) Foam nickel@SiO2@Ce 0.25 Zr 0.75 O2 was placed in a 100 mL aqueous solution containing 0.145 g nickel nitrate hexahydrate, 0.146 g cobalt nitrate hexahydrate and 0.025 g hydrazine hydrate, stirred for 30 min, and then the sample and the mixed solution were transferred to a polytetrafluoroethylene liner and subjected to a hydrothermal treatment in an oven at a temperature of 120 ° C for 10 h. After the reaction was completed, the sample was taken out, washed with deionized water and vacuum dried to obtain foamed nickel@SiO2@Ce 0.25 Zr 0.75 O2 / NiCo.

[0051] The photothermal catalytic CO2 reduction experiment was carried out in a concentrated photothermal system using the catalysts prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2. The specific steps are as follows: 100 mg of quartz wool was placed in a tripod-type stainless steel high-pressure reactor, and then the monolithic catalyst was placed on the quartz wool, 2 mL of ultrapure water was added as a reducing agent, and then the reaction gas was passed into the reactor for 20 minutes to exhaust the air in the reactor, wherein the reaction gas consisted of 1% CO2 and 99% N2. A set of Fresnel lenses was used to focus the xenon light source, so that the light intensity was increased to 4.31 W / cm 2 , the photocatalytic CO2 reduction reaction was carried out for 60 minutes, and the gas components of the reaction products were detected and analyzed by gas chromatograph (GC-9860).

[0052] Table 1. Performance of photothermal CO2 reduction of different catalysts (unit: μmol·g -1 ·h-1 )

[0053]

[0054]

[0055] The results are shown in Table 1. Compared with Example 1 and Example 2, it can be found that the cerium-zirconium ratio of the cerium-zirconium solid solution in the photothermal catalytic layer has a significant effect on the photothermal catalytic CO2 reduction performance. This is because different cerium contents affect the degree of lattice distortion of zirconium dioxide, thereby producing lattice defects with different reaction activities. Compared with Example 1 and Example 3, it can be found that the addition of non-precious metal co-catalyst Co in the photothermal catalytic layer is beneficial to increasing the proportion of reduction product CH4. This is because the co-catalyst Co enhances the decomposition of H2O, thereby promoting the further hydrogenation of the reduction product CO to CH4.

[0056] In comparative example 1, the thermal insulation layer is removed, and its yield is significantly reduced. This is because the catalyst of the present invention is provided with a thermal insulation layer in its structure, which reduces the activation energy of the photocatalytic reaction through the photothermal effect, thereby promoting CO2 reduction; in comparative example 2, the thermal insulation layer is replaced with SiO2, and the yield is significantly reduced compared with Example 3. This is because the present invention uses magnesium oxide with basic sites, which can not only serve as a thermal insulation layer to improve the photothermal effect, but also strengthen the adsorption of the reactant molecule CO2, thereby improving the performance of the photocatalytic CO2 reduction reaction, achieving a synergistic effect. Therefore, the monolithic catalyst of the present invention can be used in a concentrated photothermal system, and can utilize solar energy through the photothermal effect of the photothermal layer and the thermal insulation layer and the photoelectric effect of the photothermal catalyst layer, thereby showing excellent concentrated photothermal coupled catalytic CO2 reduction performance.

Claims

1. A multi-layer monolithic photothermal catalyst, characterized in that: The catalyst comprises a photothermal conversion layer, a thermal insulation layer and a photothermal catalytic layer from the inside to the outside, wherein the photothermal conversion layer is nickel foam, the thermal insulation layer is magnesium oxide, and the photothermal catalytic layer is a cerium-zirconium solid solution containing a promoter.

2. The multi-layered monolithic photothermal catalyst according to claim 1, characterized in that: The promoter is one or a combination of two of the non-precious metals nickel, copper, cobalt, iron or manganese.

3. The multi-layered monolithic photothermal catalyst according to claim 2, characterized in that: The molar ratio of the nickel foam, magnesium oxide, cerium-zirconium solid solution and promoter is 1000-10000:10-100:5-15:0.5-1.

5.

4. The multi-layered monolithic photothermal catalyst according to claim 1, characterized in that: The photothermal conversion layer is a porous skeleton open structure with a large number of connecting holes, the thermal insulation layer is a nano-sheet structure, and the photothermal catalytic layer is irregular nanoparticles; the photothermal conversion layer, the thermal insulation layer and the photothermal catalytic layer are connected by chemical bonds.

5. A method for preparing the multi-layer monolithic photothermal catalyst according to claim 1, characterized in that: The following steps are involved: (1) placing nickel foam in a magnesium chloride aqueous solution, adjusting the pH value of the solution, stirring, taking out and performing high-temperature annealing in a nitrogen atmosphere to obtain nickel foam@magnesium oxide; (2) placing the nickel@magnesium oxide foam obtained in step (1) in a mixed solution of cerium nitrate, zirconium oxychloride and sodium hydroxide, stirring the mixture thoroughly and then performing a hydrothermal treatment. After the reaction is completed, the mixture is taken out and washed and dried to obtain a nickel@magnesium oxide foam@cerium-zirconium solid solution; (3) placing the nickel foam @ magnesium oxide @ cerium zirconium solid solution obtained in step (2) in a mixed solution of non-precious metals and hydrazine hydrate, stirring the reaction sufficiently and then performing hydrothermal treatment. After the reaction is completed, the solid solution is taken out and washed and dried to obtain an integral catalyst for photothermal catalytic CO2 reduction.

6. The preparation method according to claim 5, characterized in that: In step (1), the solution pH is adjusted to 9-11, the stirring time is 1-5 hours, the concentration of the magnesium chloride aqueous solution is 0.1-1.0 mol / L, and the annealing temperature is 150-250° C. and the time is 1-5 hours.

7. The preparation method according to claim 5, characterized in that: In step (2), the molar ratio of cerium nitrate to zirconium oxychloride is 1:1-3, the molar ratio of the total molar ratio of cerium nitrate and zirconium oxychloride to sodium hydroxide is 1:1-3, and the stirring time is 1-5 hours; the temperature of the hydrothermal treatment is 100-200°C, and the time is 4-8 hours.

8. The preparation method according to claim 5, characterized in that: In step (3), the molar ratio of the non-precious metal to hydrazine hydrate is 1:1-3; the temperature of the hydrothermal treatment is 100-140° C., and the time is 8-12 hours.

9. Use of the multi-layered monolithic photothermal catalyst according to claim 1 in preparing hydrocarbon fuels in a concentrated photothermal system.

10. The use according to claim 9, characterized in that: The multi-layered integral photothermal catalyst is used for photothermal catalytic CO2 reduction reaction to prepare hydrocarbon fuels.

Citation Information

Patent Citations

  • Method for photothermal decomposition of H2O and / or CO2 from cerium oxide solid solution containing trace precious metals

    CN104418300A

  • Method for preparing synthesis gas by photothermal catalytic decomposition of hydrogen sulfide and carbon dioxide

    CN115583630A

  • Integral frequency division photo-thermal synergistic catalyst and preparation method and application thereof

    CN116689020A

  • Catalyst for synthesizing green methanol by coupling biomass gasification with renewable energy hydrogen production as well as preparation method and application of catalyst

    CN117282432A

  • Photocatalytic element

    WO2017061124A1